Back Cover: Micro Nozzle Assisted Spraying Process for Re‐crystallization of Submicrometer Hexanitrostilbene Explosive (Prop., Explos., Pyrotech. 7/2018). Issue 7 (18th July 2018) - Gupta, Shallu; Kumar, Pal Dinesh; Jindal, Deepika; Sharma, Sandeep; Agarwal, Arun; Lata, Prem
Abstract : The back cover picture shows a micro nozzle assisted spraying process (MNASP) for recrystallization of submicrometer HNS (sm‐HNS) explosive. The process attributes such as stirring rate, pressure, temperature, nozzle diameter, flow rate, ultra‐sonication frequency were optimized using weighted average method of Analytical Network Process (ANP) techniques. The flow parameters such as droplet size, velocity profile at different time steps of 0.001 s and droplet sauter mean diameter (D32 ) at the nozzle exit was simulated using Fluid Flow (Fluent) module of Ansys software. Particle size in the range of 300 to 700 nm, with average particle size of 515 nm and narrow standard deviation of 34 nm is obtained using this process. The process is a unique laboratory scale table‐top pilot plant high batch‐to‐batch repeatability under same condition, and cost‐effective for large scale production at the rate of 50 grams per hour. The advantage of consistency in preparation of sm‐HNS with narrow particle size distribution is observed in performance of exploding foil initiators and other HNS based explosive devices. Details are discussed in the article by Pal Dinesh Kumar et al. on page 721 ff.